156k views
3 votes
Determine which quadrant the angle Ф lies and the reference angle.

Then, find the indicated ratio for Ф' (must be an exact value).
Finally, determine the value for the original expression using the quadrants.

csc
\cfrac{4\pi }{3}

2 Answers

9 votes


\\ \rm\Rrightarrow csc(4\pi)/(3)


\\ \rm\Rrightarrow csc\left(\pi +(\pi)/(3)\right)

  • So it lies in Q3 and it's reference angle is π/3
  • Reference angle like usual lies in Q1 .

Now for value


\\ \rm\Rrightarrow csc\left(\pi+(\pi)/(3)\right)

  • In Q1 All are positive
  • In Q2 sine and cosec are positive .
  • In. Q3 tan and cot are positive .
  • In Q4 cos and sec are positive.

As it lies in Q3 it's negative


\\ \rm\Rrightarrow csc\left(-(\pi)/(3)\right)


\\ \rm\Rrightarrow -csc(\pi)/(3)


\\ \rm\Rrightarrow -(2)/(√(3))

User Munawar
by
5.0k points
5 votes

Answer:


\csc \left((4\pi)/(3)\right)=-(2)/(√(3))

Explanation:


\phi=(4 \pi)/(3)

Therefore, this angle lies in quadrant III since it is between π and 3π/2

It's reference angle is:


(4 \pi)/(3)-\pi=(\pi)/(3)

and so lies in quadrant I


\csc (\phi)=(1)/(\sin(\phi))

For sine, quadrant I and II are positive and quadrant III and IV are negative.

Therefore, as
\sin (\pi)/(3)=(√(3))/(2) then
\sin (4\pi)/(3)=-(√(3))/(2)

Finally,


\csc \left((4\pi)/(3)\right)=(1)/(\sin\left((4\pi)/(3)\right))


\implies \csc \left((4\pi)/(3)\right)=(1)/(-(√(3))/(2))


\implies \csc \left((4\pi)/(3)\right)=-(2)/(√(3))

User Elzo Valugi
by
5.0k points